2015
DOI: 10.1007/s12033-015-9888-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Expression of the Secoisolariciresinol Dehydrogenase Gene Involved in Podophyllotoxin Biosynthesis

Abstract: Podophyllotoxin (PPT) is a plant natural product that serves as a precursor for the synthesis of many well-known chemotherapeutic drugs. The limited availability and high demand for the source plants of PPT have led to the exploration of alternative sources for this compound. In this study, we utilized the endophytic fungus Phialocephala podophylli (strain PPE7) that we isolated from the rhizomes of Podophyllum peltatum and is known to produce detectable amounts of PPT in broth culture. To date, the complete P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…The entangled relationship between Mollisia and Phialocephala ( Mollisiaceae , Helotiales ), a genus comprising important root and leaf endophytes and known mostly by asexual morphs, suggests that the ecology of Mollisia species is more complex than previously assumed ( Day et al., 2012 , Tanney et al., 2016a ). Phialocephala species are saprotrophs, plant mutualists, potential plant health promoters, producers of industrially significant secondary metabolites, and infrequent causal agents of plant diseases ( Frasz et al., 2014 , Arneaud and Porter, 2015 , Wong et al., 2015 ). The most well-studied Phialocephala species belong to the P. fortinii sensu lato ( s.l.…”
Section: Introductionmentioning
confidence: 99%
“…The entangled relationship between Mollisia and Phialocephala ( Mollisiaceae , Helotiales ), a genus comprising important root and leaf endophytes and known mostly by asexual morphs, suggests that the ecology of Mollisia species is more complex than previously assumed ( Day et al., 2012 , Tanney et al., 2016a ). Phialocephala species are saprotrophs, plant mutualists, potential plant health promoters, producers of industrially significant secondary metabolites, and infrequent causal agents of plant diseases ( Frasz et al., 2014 , Arneaud and Porter, 2015 , Wong et al., 2015 ). The most well-studied Phialocephala species belong to the P. fortinii sensu lato ( s.l.…”
Section: Introductionmentioning
confidence: 99%
“…As found with the other plant-derived compounds discussed earlier, these fermentations yielded low levels in the range from 0.5 µg • L −1 to 189 µg • L −1 . However, concentrations of podophyllotoxin could sometimes increase between subculturings, suggesting the metabolite is not present due to carryover from the plant [85]. In addition, secoisolariciresinol dehydrogenase (SD) genes in the proposed podophyllotoxin biosynthetic pathway have been found in both P. peltatum and the endophyte Phialocephala podophylli (strain PPE7), with the genes characterized in vitro, the first time that the SD gene was characterized in the fungal kingdom [85].…”
Section: Podophyllotoxinmentioning
confidence: 99%
“…However, concentrations of podophyllotoxin could sometimes increase between subculturings, suggesting the metabolite is not present due to carryover from the plant [85]. In addition, secoisolariciresinol dehydrogenase (SD) genes in the proposed podophyllotoxin biosynthetic pathway have been found in both P. peltatum and the endophyte Phialocephala podophylli (strain PPE7), with the genes characterized in vitro, the first time that the SD gene was characterized in the fungal kingdom [85]. Optimization of production of podophyllotoxin requires more studies on the heterologous expression of genes in this biosynthetic pathway, and the effects of fermentation conditions will hopefully provide insight into metabolic bottlenecks and chemical signals, leading to improved endophytic production of podophyllotoxin [85].…”
Section: Podophyllotoxinmentioning
confidence: 99%
“…Two strains initially reported as Phialocephala fortinii isolated from rhizomes of Podophyllum peltatum produce podophyllotoxin, a lignan well-studied for its antiviral and antineoplastic properties (Eyberger et al 2006). The podophyllotoxin-producing strain PPE7 was referred to as Phialocephala podophylli but awaits formal description (Arneaud and Porter 2015). A Phialocephala cf.…”
Section: Endophytism Throughout Mollisiaceaementioning
confidence: 99%
“…Phialocephala species may be plant mutualists, potential biocontrol agents, producers of industrially-significant secondary metabolites, or causal agents of important plant diseases (Frasz et al 2014, Arneaud and Porter 2015, Wong et al 2015. Some studies have also reported Mollisia as endophytes of leaves and twigs in diverse host plants (Sieber 1989, Barklund and Kowalski 1996, Shamoun and Sieber 2000, Kowalski and Andruch 2012.…”
Section: Introductionmentioning
confidence: 99%